A methodological evaluation of natural user interfaces for immersive 3D Graph explorations. (February 2018) - Erra, Ugo; Malandrino, Delfina; Pepe, Luca
Highlights: A real-time 3D exploration and interaction system for graph visualization. A natural user interface for 3D interaction in a virtual reality environment. A description the 3D Graph Explorer plug-in and a presentation of the interaction design. An empirical comparison of the proposed system with the traditional mouse–keyboard combination. Abstract: In this paper, we present a novel approach for a real-time 3D exploration and interaction of large graphs using an immersive virtual reality environment and a natural user interface. The implementation of the approach has been developed as plug-in module, named 3D Graph Explorer, for Gephi, an open software for graph and network analysis. To assess the validity of the approach and of the overall environment, we have also conducted an empirical evaluation study by grouping people in two different configurations to explore and interact with a large graph. Specifically, we designed an innovative configuration, exploiting the natural user interface in a virtual reality environment, against a well-known and widespread mouse–keyboard configuration. The evaluation suggests that these upcoming technologies are more challenging than the traditional ones, but enable user to be more involved during graph interaction and visualization tasks, given the enjoyable experience elicited when combining gestures-based interfaces and virtual reality.